Efficacy of Application of Pseudocolor Filters in the Detection of Interproximal Caries - Maryam Zangooei Booshehry; Abdolrahim Davari; Fatemeh Ezoddini Ardakani; Mohammad Reza Rashidi Nejad (Tabriz University of Medical Sciences, 2010)
Background and aims. The aim of the present study was to compare the effect of application of an image processing mode of a colorizer on the efficacy of the detection of interproximal carious lesions viewed in direct digital radiography. Materials and methods. A total of 102 proximal surfaces of extracted human premolars on direct digital images were evaluated by three observers with and without the application of pseudocolor filter. The teeth were sectioned and viewed microscopically to determine the gold standard. The kappa value agreement ratios were calculated. Results. Sensitivity and specificity values for normal digital and colorized images were 66.7%, 60%, 80.5%, and 50%, respectively. However, there were no statistically significant differences between the two types of images (P = 0.12). Conclusion. In this study application of pseudocolor filter on digital radiographic images failed to result in significantly improved caries detection.